Hi there!
We can begin by identifying the moment of inertia for the objects that will rotate.
For both a uniform cylinder and disk, the moment of inertia is equivalent to:
![I = (1)/(2)MR^2](https://img.qammunity.org/2022/formulas/physics/college/kx53lvntegxa8ql4qz55g15862p5hyed1f.png)
Let:
T₁ = Tension of rope section connecting rolling cylinder to pulley
T₂ = Tension of rope section connecting hanging mass to pulley
m₁ = mass of cylinder
m₂ = mass of pulley
m₃ = mass of hanging block
a = acceleration of entire system
g = acceleration due to gravity
We can begin by doing a summation of torques about the pulley:
![\Sigma \tau = RT_2 - RT_1](https://img.qammunity.org/2022/formulas/physics/college/lek4qdm7rhjhmtutt30yy3v3tk6rqzrytd.png)
Rewrite using the rotational equivalent of Newton's Second Law:
![\Sigma \tau = I\alpha](https://img.qammunity.org/2022/formulas/physics/college/2ihfbb2ezwgeczl7bo0ltwcd3likig96yi.png)
![I\alpha = RT_2 - RT_1](https://img.qammunity.org/2022/formulas/physics/college/6hupor5bwd0rm1s9s3l0l6qzjk2w98k5vz.png)
Rewrite alpha as a/r and substitute in the moment of inertia:
![(1)/(2)M_2R^2(a)/(R) = RT_2 - RT_1](https://img.qammunity.org/2022/formulas/physics/college/8u34p857skp6cfbuzb6b3xk341lqgdnqg2.png)
Cancel out the radii:
![(1)/(2)M_2a = T_2 - T_1](https://img.qammunity.org/2022/formulas/physics/college/j8bkx7k22sv2rnpxgcovx6sufgccmyia7w.png)
Now, we must solve for each tension.
T₁
Sum torques acting on mass 1 and use the same method as above:
![\Sigma \tau = RT_1](https://img.qammunity.org/2022/formulas/physics/college/6wpmp45rhx2pfss1vvirpq4t65508fv968.png)
![(1)/(2)M_1R^2(a)/(R) = RT_1](https://img.qammunity.org/2022/formulas/physics/college/dnsyqjgw8jqd84qftrv8cu2reme2fcx2ib.png)
![(1)/(2)M_1a = T1](https://img.qammunity.org/2022/formulas/physics/college/s3200sc38vokxkyts600dewfxgeiuf8h05.png)
T₂
We can use a summation of forces:
![\Sigma F = W - T_2\\\Sigma F = m_3g - T_2\\T_2 = m_3g - m_3a](https://img.qammunity.org/2022/formulas/physics/college/jpnhpmd0wkyvjkem9cn63gis77wx5z3620.png)
Plug these derived expressions into the above:
![(1)/(2)M_2a = m_3g - m_3a - (1)/(2)M_1a\\\\](https://img.qammunity.org/2022/formulas/physics/college/guiyoahcwesj42x6o5hwtw3xvnkikdnytr.png)
Rearrange to solve for acceleration:
![a = (m_3g)/((1)/(2)M_1+(1)/(2)M_2 + m_3)](https://img.qammunity.org/2022/formulas/physics/college/46kft0npi4rzg9eit0jf3g76cplbui36yp.png)
Solve for a:
![a = ((1.40)(9.8))/((1)/(2)(0.75)+(1)/(2)(0.2) + 1.4) = 7.317 m/s^2](https://img.qammunity.org/2022/formulas/physics/college/fz6wpy5joe7vxgpias5mzkxzhrf9oyjjl1.png)
Now, we can use the following kinematic equation to solve for velocity given acceleration and distance:
![vf^2 = vi^2 + 2ad\\\\vf^2 = 2(7.317)(0.5)\\vf = √(2(7.317)(0.5)) = \boxed{2.705 m/s}](https://img.qammunity.org/2022/formulas/physics/college/iwdqj2lfsyo511l7xf5i9rxrh4c5fwc9t3.png)